Exact outage performance of two NOMA users in small-cell network over Nakagami-m fading under imperfect CSI. (27th May 2022) - Le, Chi-Bao; Nguyen, Tu-Trinh Thi; Do, Dinh-Thuan
We consider a two-user system in the scenario of relay cooperative non-orthogonal multiple access (NOMA) network with imperfections of channel state information (CSI). Firstly, on the same allocated power source, the base station (BS) transmits the superposition signal to near user and far user, which is analysed via Nakagami-m fading channels. In this situation, the near user with good channel conditions employs NOMA scheme to serve the far user. Secondly, the far user combines signals from direct link and relay link. Then, the outage performance is examined in closed-form expressions to exhibit performance gap among two NOMA users.